Oblicz wartość liczbową wyrażenia. Proszę o dokładne obliczenia.

a) 2(x-3y)² - 3(x-2y)(x-2y) + 12xy dla x = 3 i y = -1
powinno wyjść 21

b)(2x - 3y)² - x(4x+3y) - 9y² dla x = √5 - 3 i y = √5 + 3
wynik powinien być 60

z góry dzięki

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T17:20:22+02:00
2(x-3y)² - 3(x-2y)(x-2y) + 12xy= 2 (x²-6xy+9y²)-3(x²-4y²) +12xy=
2x²-12xy+18y²-3x²+12y²+12xy= -x²+30y²
x=3 y=-1

-(3)²+30*(-1)²= -9+30=21

b)(2x - 3y)² - x(4x+3y) - 9y²=
(4x²-12xy+9y²)-4x²-3xy-9y²=
4x²-12xy+9y²-4x²-3xy-9y²=
-15xy
Podstawiamy
x = √5 - 3 i y = √5 + 3
-15(5-9)=-15*(-4)=60
2010-04-06T17:29:04+02:00
A)
2(3-3(-1))²-3(3-2(-1))(3-2(-1))+12×3×(-1)
2(3+3)²-3(3+2)×3+2-36
2(9+9)-9-2×3+2-36
18+18-9-6+2-36
36-9-6+2-36
-9-6+2
-15+2
-13